Czy naukowiec ma płeć? Rozważania na temat relacji w świecie nauki przez pryzmat stereotypów płciowych - Kośnik, Konrad; Węglerska, Olga (Człowiek i Społeczeństwo, 2021)
The paper aims to study a problem of gender stereotypes present in the academic community, harming particular researchers (especially women). In the article chosen methods of stereotypes’ counteraction are focused and analysed in terms of their risks of stereotype preservation. The concept of feminatives as a proposition of gender equalization is reflected and presented from the perspective of their drawbacks in the field of social functioning. The gender stereotypes’ influence on research participants is treated as a special aspect of the problem, peculiarly in the area of human sexuality research due to specific feedback and results’ bias. The problem is analysed then both from the systemic (contextual) perspective of academia and the particular situation of research, showing that gender may but does not have to influence scientific work.